Evaluation of Factors of Regional Competitiveness - Vrtěnová Lucie (Technická univerzita v Košiciach, 2009)
This article deals with actual questions of regional competitiveness and evaluation of its factors. The influence of individual factors on regional competitiveness is not possible to be generalized. It depends on current state of a region, presence of chosen factors in a region and their interference. On the basis of this fact we can generalize regions according to basic archetypes. Afterwords we are able to determine assumed impact of individual factors. We can take use of system dynamics.
Hodnocení faktorů regionální konkurenceschopnosti
Keywords: competitiveness; factors of competitiveness; region; system dynamics; konkurenceschopnost; faktory konkurenceschopnosti; region; systémová dynamika